2019
DOI: 10.1111/nyas.13991
|View full text |Cite
|
Sign up to set email alerts
|

Retention of osteocytic micromorphology by sclerostin antibody in a concurrent ovariectomy and functional disuse model

Abstract: Prolonged mechanical unloading in bedridden patients and concurrent hormonal dysregulation represents the cause of one of the severest forms of osteoporosis, a condition for which there are very few efficacious interventions available to date. Sclerostin, a Wnt antagonist, acts as a negative regulator of bone formation. Sclerostin antibody (Scl‐Ab)–mediated blockade of sclerostin can dramatically enhance bone formation and reduce bone resorption. This study was designed to investigate the therapeutic effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…81 Osteocytes also exhibit morphological and structural abnormalities in unloaded and/or ovariectomised conditions, which may be reversed by blockade of protein sclerostin through administration of sclerostin antibodies. 82 Direct attachment of osteocytes to the surface of implanted biomaterials can also be evaluated, 74,83 and may be interpreted as an indication of osseointegration when observed at materials otherwise considered to integrate poorly, e.g., CoCr. 73,75…”
Section: Bone Imagingmentioning
confidence: 99%
“…81 Osteocytes also exhibit morphological and structural abnormalities in unloaded and/or ovariectomised conditions, which may be reversed by blockade of protein sclerostin through administration of sclerostin antibodies. 82 Direct attachment of osteocytes to the surface of implanted biomaterials can also be evaluated, 74,83 and may be interpreted as an indication of osseointegration when observed at materials otherwise considered to integrate poorly, e.g., CoCr. 73,75…”
Section: Bone Imagingmentioning
confidence: 99%
“…Sclerostin, an inhibitor of the Wnt/β-catenin signaling pathway that regulates bone growth, has emerged as an attractive therapeutic target for the treatment of osteoporosis (Suen and Qin, 2016). Dongye Zhang et al used the sclerostin antibody to retain osteocytic micromorphology and function to rescue bone mass against prolonged mechanical unloading (Zhang et al, 2017;Zhang et al, 2020), while a phase 3 trial reported that patients administered with romosozumab (sclerostin monoclonal antibody) may experience some adverse events, such as nasopharyngitis, arthralgia, and hypercalcemia (Langdahl et al, 2017). Yi-Xian Qin et al showed that low-intensity, highfrequency loading has the potential to mitigate regional bone loss induced by long-term bed rest (Qin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Changes are reversed by Scl-Ab [ 33 ] Osteoporosis Rat (± OVX) No effect of hPTH, ALN, or RLX demonstrated [ 35 ] Osteoporosis Rat (± OVX) Regular osteocyte shape, higher dendricity, and branched canaliculi under stimulation with low-magnitude high-frequency vibration during fracture healing [ 36 ] Postmenopausal osteoporosis Human No change in Ot.LCN morphology in osteoporotic vs. age-matched healthy individuals [ 29 ] Skeletal unloading Human Greater loss of dendricity in long-term immobilised vs. age-matched osteoporotic and healthy individuals [ 29 ] Hindlimb suspension Rat (± OVX) Decreased osteocyte density and dendricity in normal/healthy and OVX animals. Changes are reversed by Scl-Ab [ 33 ] Spinal cord transection Rat Lower dendricity and osteocyte density per total area, deformed and disorganised osteocytes. Changes are reversed by Scl-Ab [ 27 ] Spinal cord transection Rat Lower dendricity.…”
Section: Changes In Osteocytes Due To Ageing and Diseasementioning
confidence: 99%
“…Morphological abnormalities of the Ot.LCN such as decreased osteocyte density and reduced dendricity are observed under experimentally induced osteoporosis via ovariectomy (OVX) in rats. These alterations are reversed by the administration of sclerostin monoclonal antibody (Scl-Ab) [ 33 ] and blockade of the protein sclerostin, which is an osteocyte-secreted Wnt signalling antagonist and inhibitor of bone formation [ 34 ]. Changes in local nanomechanical properties arising from different sequential treatment regimens of various anti-osteoporotic agents, e.g., human parathyroid hormone (hPTH), alendronate (ALN), raloxifene (RLX), have been correlated with osteocyte shape descriptors (i.e., major and minor axes) and osteocyte density in healthy and OVX rats.…”
Section: Changes In Osteocytes Due To Ageing and Diseasementioning
confidence: 99%
See 1 more Smart Citation